Compressive properties and failure behavior of photocast hydroxyapatite gyroid scaffolds vary with porosity. (July 2022) - Isaacson, Nelson; Lopez-Ambrosio, Katherine; Chubb, Laura; Waanders, Nathan; Hoffmann, Emily; Witt, Connor; James, Susan; Prawel, David A
Hydroxyapatite is commonly used in tissue engineered scaffolds for bone regeneration due to its excellent bioactivity and slow degradation rate in the human body. A method of layer-wise, photopolymerized viscous extrusion, a type of additive manufacturing, was developed to fabricate hydroxyapatite gyroid scaffolds with 60%, 70%, and 80% porosities. This study uses this method to produce and evaluate calcium phosphate–based scaffolds. Gyroid topology was selected due to its interconnected porosity and superior, isotropic mechanical properties compared to typical rectilinear lattice structures. These 3D printed scaffolds were mechanically tested in compression and examined to determine the relationship between porosity, ultimate compressive strength, and fracture behavior. Compressive strength increased with decreasing porosity. Ultimate compressive strengths of the 60% and 70% porous gyroids are comparable to that of human cancellous bone, and higher than previously reported for hydroxyapatite rectilinear scaffolds. These gyroid scaffolds exhibited ultimate compressive strength increases between 1.5 and 6.5 times greater than expected, based on volume of material, as porosity is decreased. The Weibull moduli, a measure of failure predictability, were predictive of failure mode and found to be in the accepted range for engineering ceramics. The gyroid scaffolds were also found to be self-reinforcing such that initial failures due to minor manufacturing inconsistencies did not appear to be the primary cause of early failure of the scaffold. The porous gyroids exhibited scaffold failure characteristics that varied with porosity, ranging from monolithic failure to layer-by-layer failure, and demonstrated self-reinforcement in each porosity tested.